Theoretical modeling, verification, and application study on a novel bending-bending coupled piezoelectric ultrasonic transducer. (1st April 2022) - Wang, Liang; Wang, Jian-An; Jin, Jia-Mei; Yang, Lin; Wu, Shu-Wen; Zhou, Charles C.
Graphical abstract: Highlights: A novel omnidirectional ultrasonic wave piezoelectric transducer is proposed in this study. A novel transfer matrix model is created for the coupled bending vibration piezoelectric composite beam. A general electromechanical coupling model is developed for the piezoelectric transducer. Experimental investigations confirmed the validation of the piezoelectric transducer design. Abstract: Commercialized ultrasonic algae removal systems generally adopt multiple Langevin ultrasonic transducers to produce omnidirectional ultrasound radiation, leading to complex configuration and control systems, low efficiency, high energy consumption, and high cost. In order to ease these issues, a novel bending-bending coupled piezoelectric ultrasonic transducer is proposed, theoretically modeled, and experimentally investigated in this study. Two groups of piezoelectric ceramics with dual polarization zones are sandwiched between two metal blocks, which are used to produce two orthogonal and identical bending vibration modes. With the coupling of the two bending vibration modes, the proposed sandwich piezoelectric transducer can produce omnidirectional ultrasonic irradiation for algae removal, which can greatly simplify the configuration and control system of ultrasonic algae removal system, lower energy consumption, and improve removal efficiency. A novel transfer matrix model of describing the bending-bending coupled vibration is first created for the combined piezoelectric element with dual polarization zones by simultaneously considering its electrical and mechanical properties. Then an electromechanical coupling model of the proposed transducer is developed to reveal its dynamic behavior. In addition, the vibration characteristics of the transducer prototype are tested, in order to verify the feasibility of the transducer design and operating principle and to confirm the correctness of the developed electromechanical coupling model. Finally, an application study is carried out to evaluate the algae removal effect of the proposed transducer prototype. At ultrasonic intensities of 0.014 W/mL and 0.021 W/mL, the algal removal rate, respectively, reached 45.83% and 63.27% when the ultrasonic irradiation time was 60 min, presenting efficient algae removal effect. Compared to the traditional Langevin ultrasonic transducers, the proposed transducer can achieve omni-directional ultrasonic radiation, greatly simplifying the structure and drive circuit of the ultrasonic algae removing system. It has a good application prospect in the field of environmental protection and water purification.